HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP MAHASISWI FK UPN VETERAN JAKARTA TERHADAP MINAT VAKSINASI HPV SEBAGAI UPAYA PENCEGAHAN KANKER SERVIKS - Puteri Beta Meidina Yunus, (2022)
The incidence of cervical cancer in Indonesia ranks second highest in Indonesia. The factor of lack of public awareness can be the cause of the high rate of cervical cancer. The perfect prevention strategy can facilitate the decline in cervical cancer rates. One of the efforts to prevent cervical cancer can be done by giving the HPV vaccine. This study aims to determine the relationship between the level of knowledge and attitudes of female medical college students of UPN Veteran Jakarta to the interest in HPV vaccination as an effort to prevent cervical cancer. This type of research uses an observational analytic study with a cross-sectional design. The number of samples as many as 97 students of the Faculty of Medicine UPN Veteran Jakarta were taken using the Proportionate Stratified Random Sampling technique. Data analysis was processed by logistic regression. There was a significant relationship (p-value < 0.05) with interest in HPV vaccination as an effort to prevent cervical cancer, namely the level of knowledge of cervical cancer (p-value 0.006; CI 1.438-10.595), the level of knowledge of HPV vaccine (p-value 0.023; CI 1,127-5,875), and attitudes toward HPV vaccination (p-value 0,000; CI 11,597-121,906). The most dominant factor was attitude towards HPV vaccination (OR 45,047; CI 12,491-162,460). Students with good attitudes have the highest chance of increasing interest in HPV vaccination. The conclusion of the study is that there is a significant relationship between the level of knowledge and attitudes of female medical college students of UPN Veteran Jakarta with interest in HPV vaccination as an effort to prevent cervical cancer.